2020
DOI: 10.3324/haematol.2020.266676
|View full text |Cite
|
Sign up to set email alerts
|

Protein-L-isoaspartate O-methyltransferase is required for <i>in vivo</i> control of oxidative damage in red blood cells

Abstract: Red blood cells have the special challenge of a large amount of reactive oxygen species (from their substantial iron load and Fenton reactions) combined with the inability to synthesize new gene products. Considerable progress has been made in elucidating the multiple pathways by which red blood cells neutralize reactive oxygen species via NADPH driven redox reactions. However, far less is known about how red blood cells repair the inevitable damage that does occur when reactive oxygen species break through an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Methionine supplementation and consumption were comparable in normoxic and hypoxic RBCs, showing similar trends with respect to the accumulation of SAM as a function of storage. However, lower SAM and higher SAH at storage day 7—as a result of methylation events consuming methyl-groups ( D’alessandro et al, 2021b ) —was only observed in hypoxic RBCs, which were also characterized by higher levels of methionine S-oxide and 5 methylthioadenosine, as well as decreased markers of purine oxidation (hypoxanthine, xanthine) and higher levels of antioxidant urate ( Figure 5 ). Hypoxia also drove differential lysine and creatine (higher levels than normoxic RBCs) and arginine (lower in hypoxic RBCs than controls— Figure 5 ), with no significant increases in ornithine, citrulline, or polyamines (not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methionine supplementation and consumption were comparable in normoxic and hypoxic RBCs, showing similar trends with respect to the accumulation of SAM as a function of storage. However, lower SAM and higher SAH at storage day 7—as a result of methylation events consuming methyl-groups ( D’alessandro et al, 2021b ) —was only observed in hypoxic RBCs, which were also characterized by higher levels of methionine S-oxide and 5 methylthioadenosine, as well as decreased markers of purine oxidation (hypoxanthine, xanthine) and higher levels of antioxidant urate ( Figure 5 ). Hypoxia also drove differential lysine and creatine (higher levels than normoxic RBCs) and arginine (lower in hypoxic RBCs than controls— Figure 5 ), with no significant increases in ornithine, citrulline, or polyamines (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Methionine was indeed found to feed oxidant stress-induced isoaspartyl-protein damage repair through the activity of the enzyme PIMT. Genetic ablation of PIMT does result in RBCs that are more susceptible to intra- and extra-vascular hemolysis following oxidant stress in vitro and in vivo ( D’alessandro et al, 2021b ). Supplementation of methionine to the additive solution would thus not only provide a direct scavenger of ROS, but also fuel repairing of oxidatively damaged RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Guinea pig RBCs demonstrated significant alterations in the levels of methyl-group donors [similar to humans with G6PD deficiency ( Ingrosso et al, 2002 )]. Guinea pig RBCs were also characterized by higher levels of the byproducts of methylation events (e.g., S -adenoyslhomocysteine), a pathway that in RBCs is activated to repair oxidant stress-induced isoaspartyl damage to proteins ( D’Alessandro et al, 2021b ). Similarly, guinea pig RBCs showed significantly higher levels (and faster accumulation rates) of oxidized purines as a function of storage duration; this pathway depends on oxidant-stress induced breakdown and/or deamination of high-energy purines, which negatively correlates with the capacity of stored human or rodent RBCs to circulate following transfusion ( Nemkov et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…As such, increases in polyamines may be compensating for the decreased membrane stability characteristic of PKD associated hemolytic anemia. Polyamines also play a role in direct scavenging of reactive oxygen species, in like fashion to sulfur-containing compounds methionine ( D’Alessandro et al, 2020a ) and taurine ( Bertolone et al, 2020 ), both increasing significantly in PKD subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Though limited in scope (i.e., small cohort with a single genetic mutation R479H), the study addresses the need for basic science to investigate pathologies targeting underrepresented minorities (four out of five PKD subjects were from Amish families), with the ultimate goal to target treatments to health disparities ( Hunter et al, 2021 ). Indeed, since these subjects suffer from anemia and therapeutic options are limited (e.g., recurring transfusions), this study could pave the way to targeted personalized investigations to drive interventions, such as supplementation of antioxidants (taurine; Bertolone et al, 2020 ; methionine, and choline for isoaspartyl protein damage-repair; D’Alessandro et al, 2020a ); carnitine supplementation ( Nikolaos et al, 2000 ) and dietary interventions to sustain membrane lipid remodeling in response to increased oxidant stress.…”
Section: Discussionmentioning
confidence: 99%